A method for the production of lightweight concrete

CN120535277BActive Publication Date: 2026-11-03CHINA MCC17 GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510623125.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2026-11-03
Estimated Expiration
2045-05-15

AI Technical Summary

Technical Problem

Existing lightweight concrete technology has limited application in structural parts that meet the requirements of lightweight and high strength, and the production process is energy-intensive and costly, making it difficult to achieve effective secondary utilization of solid waste resources.

Method used

Lightweight concrete is prepared by using solid waste-based composite cementitious materials, non-fired ceramsite, and iron tailings sand as the main raw materials, combined with polycarboxylate superplasticizer, and by stirring. Non-fired ceramsite and cementitious materials are prepared using industrial solid waste such as fly ash, iron tailings, and desulfurized gypsum to reduce the density of concrete and increase its strength.

Benefits of technology

It enables the low-density, high-strength, and low-cost production of lightweight concrete, which aligns with the concept of sustainable development and possesses excellent construction performance, making it suitable for building scenarios with special requirements for weight and strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535277B_ABST
    Figure CN120535277B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of lightweight concrete and belongs to the technical field of concrete. The preparation method comprises the following raw materials in parts by weight: 400-500 parts of solid waste-based composite cementitious material, 600-800 parts of baking-free ceramic granules, 500-600 parts of iron tailing sand, 100-200 parts of water and 5-7 parts of water reducing agent. The baking-free ceramic granules are prepared without high-temperature sintering, so that the energy consumption and production cost are reduced; the solid waste-based composite cementitious material reduces the cement consumption and cost; the concrete prepared from the two has low density, the compressive strength and crack resistance of the concrete are improved, the secondary utilization of solid waste resources is realized, and environmental pollution is reduced; finally, the water reducing agent has more hydroxyl groups and contains a naphthalene ring, so that the water mixing amount and internal porosity of the concrete are reduced, and the strength of the concrete is improved; in conclusion, the prepared concrete is suitable for building scenes with special requirements on weight and strength, and has important application value in the technical field of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete technology, and specifically relates to a method for preparing lightweight concrete. Background Technology

[0002] The construction and mining industries generate a large amount of solid waste. Processing this solid waste yields ultrafine solid waste powder, which can solve the problem of solid waste disposal and also protect the environment. In the secondary utilization of this ultrafine solid waste powder, it can be combined with clay materials to prepare lightweight concrete quick-setting grout. This grout can then be used to cast precast components. Current lightweight concrete technology uses ordinary concrete with a density of 2350 kg / m³. 3 -2450kg / m 3 The strength is 30 MPa; it is usually composed of cement, water, sand, and gravel. For example, the mix ratio of C25 is: cement:sand; gravel:water = 1:1.40:2.85:0.47 (mass ratio). Concrete prepared using this method has a relatively high density, making it unsuitable for structural components requiring lightweight concrete. Currently, the density of lightweight aggregate concrete is generally 1850 kg / m³. 3 However, it is still not applicable to concrete with a strength greater than C20 and a density less than 1500 kg / m³. 3 Structural components. For example, Chinese patent CN104844099B, "A Low-Shrinkage, Low-Viscosity, Ultra-High-Strength Concrete," describes a concrete made by mixing cement, microspheres, mineral powder, manufactured sand, and crushed stone. Although the concrete has a high strength grade, its density reaches 2400 kg / m³. 3 This results in a high apparent density in the concrete. Based on the above problems, this invention proposes a method for preparing lightweight concrete. Summary of the Invention

[0003] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing lightweight concrete.

[0004] The objective of this invention can be achieved through the following technical solutions:

[0005] A method for preparing lightweight concrete includes the following steps:

[0006] Step 1: Pour the solid waste-based composite cementitious material, non-fired ceramsite, and iron tailings sand into a concrete mixer and mix for 1-2 minutes;

[0007] Step 2: Add water and water-reducing agent to the mixer from Step 1, and continue mixing for 1-2 minutes to obtain lightweight concrete.

[0008] Furthermore, the raw materials are as follows by weight: 400-500 parts solid waste-based composite cementitious material, 600-800 parts non-fired ceramsite, 500-600 parts iron tailings sand, 100-200 parts water and 5-7 parts water-reducing agent.

[0009] Furthermore, the iron tailings sand in step two is used as fine aggregate with a fineness modulus of 2.55 and a particle size range of 0.15-4.75 mm.

[0010] Furthermore, the non-fired ceramsite is prepared through the following steps:

[0011] Step A1: Place the ground fly ash, iron tailings and desulfurized gypsum in an oven at 60-80℃ and dry them to constant weight. After cooling, you will get the dried fly ash, iron tailings and desulfurized gypsum.

[0012] Step A2: Mix the dried fly ash, dried iron tailings, dried desulfurized gypsum, quicklime and sodium silicate evenly to obtain the basic materials for preparing ceramsite.

[0013] Step A3: Turn on the disc granulator, sprinkle a small amount of the basic material obtained in step A2 on the top of the disc granulator, fix the angle of the pelletizing disc at 60°, control the rotation speed at 40-50 r / min, add water to the material in the granulator with a spray bottle, observe the degree of material adhesion, and then continue to add the remaining basic material and water to the granulator to obtain pelletized ceramsite.

[0014] Step A4: Remove the pelletized ceramsite from the pelletizing tray and allow it to cure. Once the ceramsite has stabilized, place it in a square-hole sieve with different aperture sizes for sieving to obtain non-fired ceramsite.

[0015] Furthermore, the raw materials are as follows by mass: 38-42 parts dried fly ash, 38-42 parts dried iron tailings, 8-12 parts dried desulfurized gypsum, 4-6 parts quicklime, and 4-6 parts sodium silicate.

[0016] Furthermore, in step A3, the small amount of basic material is 1 / 10 of the total mass of the basic material.

[0017] Further, the fly ash comprises the following components by mass fraction: 50.70% SiO2, 36.43% Al2O3, 4.48% CaO, 0.38% MgO, 1.69% TiO2, 1.14% K2O, and 4.8% LOI.

[0018] Furthermore, the iron tailings comprises the following components by mass fraction: 45.69% SiO2, 7.42% Al2O3, 22.73% CaO, 9.99% MgO, 45.69% SiO2, 0.21% K2O, 3.57% LOI, 9.67% Fe2O3, and 0.10% SO3.

[0019] Furthermore, the solid waste-based composite cementitious material is prepared through the following steps:

[0020] The slag powder is dried in an oven at 60-80℃. The dried slag powder is then mixed evenly with steel slag, cement, and desulfurized gypsum to obtain a solid waste-based composite cementitious material.

[0021] Furthermore, the raw materials are as follows by weight: 48-52 parts dried slag powder, 8-12 parts steel slag, 28-32 parts cement, and 8-12 parts desulfurized gypsum.

[0022] Furthermore, the water-reducing agent is prepared through the following steps:

[0023] Step B1: Weigh viscous acid and 2-naphthylamine as reactants, and add them together with N,N-dimethylformamide into a three-necked flask equipped with a magnetic stirrer, a condenser, and a thermometer. After stirring and mixing, add dicyclohexylcarbodiimide to the system. Place the reaction apparatus in a constant temperature water bath at 45°C and continue the reaction for 5 hours. After the reaction is complete, filter, remove part of the solvent by vacuum distillation, and then purify by silica gel column chromatography (the eluent is petroleum ether and ethyl acetate, with a volume ratio of 4:1). Remove the eluent by rotary evaporation to obtain reaction product 1.

[0024] The reaction principle of step B1 is as follows: Under the catalysis of dicyclohexylcarbodiimide, the amino group in the 2-naphthylamine molecule undergoes an amidation reaction with the carboxyl group on the viscous acid. By adjusting the molar ratio of the two to approximately 1:1 (with a slight excess of viscous acid), only one carboxyl group in the viscous acid molecule undergoes the amidation reaction; the reaction formula is as follows:

[0025]

[0026] Step B2: Weigh reaction product 1 and allylamine as reaction raw materials, and add them together with N,N-dimethylformamide into a three-necked flask equipped with a magnetic stirrer, a condenser and a thermometer. After stirring and mixing, add dicyclohexylcarbodiimide to the system. Place the reaction apparatus in a constant temperature water bath at 55°C and continue the reaction for 7 hours. After the reaction is complete, filter, remove part of the solvent by vacuum distillation, and then purify by silica gel column chromatography (the eluent is petroleum ether and ethyl acetate, with a volume ratio of 5:1). Remove the eluent by rotary evaporation to obtain reaction product 2.

[0027] The reaction principle of step B2 is as follows: under the catalysis of dicyclohexylcarbodiimide, the amino group in the allylamine molecule undergoes an amidation reaction with the carboxyl group on reaction product 1; the reaction formula is as follows:

[0028]

[0029] Step B3: Weigh isobutylene polyoxyethylene ether, isopentenyl alcohol polyoxyethylene ether, and deionized water and add them to a four-necked flask equipped with a magnetic stirrer, condenser, and thermometer. Stir continuously to dissolve. Weigh L-ascorbic acid, mercaptoacetic acid, and deionized water and mix them as material A. Weigh acrylic acid and deionized water and mix them as material B. Add ammonium persulfate and reaction product 2 to the four-necked flask. After stirring for 15 minutes, start adding materials A and B dropwise. The dropwise addition time is 4 hours. After the dropwise addition is completed, keep the temperature at 45°C for 3 hours. Stop the temperature holding to obtain the water-reducing agent.

[0030] Furthermore, in step B1, the ratio of the amounts of viscous acid, 2-naphthylamine, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 23.7g:14.3g:100mL:20.6g.

[0031] Furthermore, in step B2, the ratio of reaction product 1, allylamine, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 33.5g:5.7g:100mL:20.6g.

[0032] Furthermore, in step B3, the ratio of the amounts of isobutylene polyoxyethylene ether, isopentenyl alcohol polyoxyethylene ether, ascorbic acid, mercaptoacetic acid, acrylic acid, ammonium persulfate, and reaction product 2 is 50.0g:25.0g:3.7g:1.3g:11.3g:2.2g:9.7g.

[0033] The beneficial effects of this invention are:

[0034] 1. The preparation process of this invention makes extensive use of industrial solid waste (such as fly ash, iron tailings, desulfurization gypsum, steel slag, slag powder, etc.), realizing the secondary utilization of solid waste resources, reducing environmental pollution, and conforming to the concept of sustainable development.

[0035] 2. The lightweight concrete prepared by using non-fired ceramsite and solid waste-based composite cementitious materials has a significantly lower density than ordinary concrete.

[0036] 3. In the interface transition zone of concrete, the aggregate and cement paste are tightly bonded, there are more hydration products, and the mechanical interlocking effect is strong, which improves the compressive strength and crack resistance of concrete.

[0037] 4. The slump of the concrete is between 140-200mm, with moderate fluidity, making it easy to construct and pour.

[0038] 5. The preparation of non-fired ceramsite does not require high-temperature sintering, which reduces energy consumption and production costs; solid waste-based cementitious materials reduce cement usage, further reducing costs;

[0039] 6. The prepared water-reducing agent is a polycarboxylate water-reducing agent. Compared with the traditional polycarboxylate water-reducing agents on the market, it has more hydroxyl groups and contains naphthalene rings, which increases the contact area between concrete and water, allows the concrete to be fully hydrated, reduces the amount of water to mix, reduces the internal porosity of the concrete, and improves the strength of the concrete.

[0040] In summary, the lightweight concrete produced by this invention combines environmental friendliness, lightweight, high strength, and good workability with low cost, making it suitable for construction scenarios with special requirements for weight and strength. It has significant application value in the field of concrete technology. Attached Figure Description

[0041] The invention will now be further described with reference to the accompanying drawings.

[0042] Figure 1 This is a schematic diagram of concrete slump from Embodiments 10-14 of the present invention;

[0043] Figure 2 This is a schematic diagram of the compressive strength of embodiments 10-14 of the present invention;

[0044] Figure 3 This is a schematic diagram of the total crack area in embodiments 10-14 of the present invention;

[0045] Figure 4 a is a diagram illustrating the failure morphology of the lightweight concrete of this invention; Figure 4 b is a diagram of the failure modes of ordinary concrete. Detailed Implementation

[0046] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0047] Example 1

[0048] Preparation of non-fired ceramsite:

[0049] Step A1: Place the ground fly ash, iron tailings and desulfurized gypsum in an oven at 60℃ and dry to constant weight. After cooling, the dried fly ash, iron tailings and desulfurized gypsum are obtained.

[0050] Step A2: Mix 38g of dried fly ash, 38g of dried iron tailings, 12g of dried desulfurized gypsum, 6g of quicklime and 6g of sodium silicate evenly to obtain the basic materials for preparing ceramsite.

[0051] Step A3: Turn on the disc granulator and sprinkle the basic material obtained in step A2 (1 / 10 of the total mass) on top of the disc granulator. The angle of the pelletizing disc is fixed at 60° and the rotation speed is controlled at 40 r / min. Add water to the material in the granulator with a spray bottle and observe the degree of material adhesion. Then continue to add the remaining basic material and water to the granulator to obtain pelletized ceramsite.

[0052] Step A4: Remove the pelletized ceramsite from the pelletizing tray and allow it to cure. Once the ceramsite has stabilized, place it in a square-hole sieve with different aperture sizes for sieving to obtain non-fired ceramsite.

[0053] The fly ash comprises the following components by mass fraction: 50.70% SiO2, 36.43% Al2O3, 4.48% CaO, 0.38% MgO, 1.69% TiO2, 1.14% K2O, and 4.8% LOI.

[0054] The iron tailings comprise the following components by mass fraction: 45.69% SiO2, 7.42% Al2O3, 22.73% CaO, 9.99% MgO, 45.69% SiO2, 0.21% K2O, 3.57% LOI, 9.67% Fe2O3, and 0.10% SO3.

[0055] Example 2

[0056] Preparation of non-fired ceramsite:

[0057] Step A1: Place the ground fly ash, iron tailings and desulfurized gypsum in an oven at 60℃ and dry to constant weight. After cooling, the dried fly ash, iron tailings and desulfurized gypsum are obtained.

[0058] Step A2: Mix 42g of dried fly ash, 42g of dried iron tailings, 8g of dried desulfurized gypsum, 4g of quicklime and 4g of sodium silicate evenly to obtain the basic materials for preparing ceramsite.

[0059] Step A3: Turn on the disc granulator and sprinkle the basic material obtained in step A2 (1 / 10 of the total mass) on top of the disc granulator. The angle of the pelletizing disc is fixed at 60° and the rotation speed is controlled at 40 r / min. Add water to the material in the granulator with a spray bottle and observe the degree of material adhesion. Then continue to add the remaining basic material and water to the granulator to obtain pelletized ceramsite.

[0060] Step A4: Remove the pelletized ceramsite from the pelletizing tray and allow it to cure. Once the ceramsite has stabilized, place it in a square-hole sieve with different aperture sizes for sieving to obtain non-fired ceramsite.

[0061] The fly ash comprises the following components by mass fraction: 50.70% SiO2, 36.43% Al2O3, 4.48% CaO, 0.38% MgO, 1.69% TiO2, 1.14% K2O, and 4.8% LOI.

[0062] The iron tailings comprise the following components by mass fraction: 45.69% SiO2, 7.42% Al2O3, 22.73% CaO, 9.99% MgO, 45.69% SiO2, 0.21% K2O, 3.57% LOI, 9.67% Fe2O3, and 0.10% SO3.

[0063] Example 3

[0064] Preparation of non-fired ceramsite:

[0065] Step A1: Place the ground fly ash, iron tailings and desulfurized gypsum in an oven at 80℃ and dry to constant weight. After cooling, the dried fly ash, iron tailings and desulfurized gypsum are obtained.

[0066] Step A2: Mix 40g of dried fly ash, 40g of dried iron tailings, 10g of dried desulfurized gypsum, 5g of quicklime and 5g of sodium silicate evenly to obtain the basic materials for preparing ceramsite.

[0067] Step A3: Turn on the disc granulator and sprinkle the basic material obtained in step 2 (1 / 10 of the total mass) on the top of the disc granulator. The angle of the pelletizing disc is fixed at 60° and the rotation speed is controlled at 50 r / min. Add water to the material in the granulator with a spray bottle and observe the degree of material adhesion. Then continue to add the remaining basic material and water to the granulator to obtain pelletized ceramsite.

[0068] Step A4: Remove the pelletized ceramsite from the pelletizing tray and allow it to cure. Once the ceramsite has stabilized, place it in a square-hole sieve with different aperture sizes for sieving to obtain non-fired ceramsite.

[0069] The fly ash comprises the following components by mass fraction: 50.70% SiO2, 36.43% Al2O3, 4.48% CaO, 0.38% MgO, 1.69% TiO2, 1.14% K2O, and 4.8% LOI.

[0070] The iron tailings comprise the following components by mass fraction: 45.69% SiO2, 7.42% Al2O3, 22.73% CaO, 9.99% MgO, 45.69% SiO2, 0.21% K2O, 3.57% LOI, 9.67% Fe2O3, and 0.10% SO3.

[0071] Example 4

[0072] Preparation of solid waste-based composite cementitious materials:

[0073] The slag powder was dried in an oven at 60°C. 52g of dried slag powder was then mixed evenly with 12g of steel slag, 28g of cement (42.5 grade commercial cement) and 8g of desulfurized gypsum to obtain a solid waste-based composite cementitious material.

[0074] Example 5

[0075] Preparation of solid waste-based composite cementitious materials:

[0076] The slag powder was dried in an oven at 60°C. 48g of dried slag powder was then mixed evenly with 8g of steel slag, 32g of cement (42.5 grade commercial cement) and 12g of desulfurized gypsum to obtain a solid waste-based composite cementitious material.

[0077] Example 6

[0078] Preparation of solid waste-based composite cementitious materials:

[0079] The slag powder was dried in an oven at 80℃. 50g of the dried slag powder was then mixed evenly with 10g of steel slag, 30g of cement (42.5 grade commercial cement) and 10g of desulfurized gypsum to obtain a solid waste-based composite cementitious material.

[0080] Example 7

[0081] Preparation of water-reducing agent:

[0082] Step B1: Weigh 23.7g of viscous acid and 14.3g of 2-naphthylamine as reaction raw materials, and add them together with 100mL of N,N-dimethylformamide into a three-necked flask equipped with a magnetic stirrer, a condenser and a thermometer. After stirring and mixing, add 20.6g of dicyclohexylcarbodiimide to the system. Place the reaction apparatus in a constant temperature water bath at 45℃ and continue the reaction for 5 hours. After the reaction is complete, filter, remove part of the solvent by vacuum distillation, and then purify by silica gel column chromatography (the eluent is petroleum ether and ethyl acetate, with a volume ratio of 4:1). Remove the eluent by rotary evaporation to obtain reaction product 1.

[0083] Step B2: Weigh 33.5g of reaction product 1 and 5.7g of allylamine as reaction raw materials, and add them to a three-necked flask equipped with a magnetic stirrer, condenser and thermometer along with 100mL of N,N-dimethylformamide. After stirring and mixing, add 20.6g of dicyclohexylcarbodiimide to the system. Place the reaction apparatus in a constant temperature water bath at 55℃ and continue the reaction for 7h. After the reaction is complete, filter, remove part of the solvent by vacuum distillation, and then purify by silica gel column chromatography (the eluent is petroleum ether and ethyl acetate, with a volume ratio of 5:1). Remove the eluent by rotary evaporation to obtain reaction product 2.

[0084] Step B3: Weigh 50.0g of isobutylene polyoxyethylene ether (molecular weight 5000), 25.0g of isopentenyl alcohol polyoxyethylene ether (molecular weight 5000), and 150mL of deionized water and add them to a four-necked flask equipped with a magnetic stirrer, a condenser, and a thermometer. Stir continuously to dissolve. Weigh 3.7g of L-ascorbic acid, 1.3g of mercaptoacetic acid, and 50mL of deionized water and mix them as material A. Weigh 11.3g of acrylic acid and 50mL of deionized water and mix them as material B. Add 2.2g of ammonium persulfate and 9.7g of reaction product 2 to the four-necked flask. After stirring for 15 minutes, start adding materials A and B dropwise. The dropwise addition time is 4 hours. After the dropwise addition is completed, keep the temperature at 45℃ for 3 hours. Stop the temperature holding to obtain the water-reducing agent.

[0085] Example 8

[0086] Step 1: Pour 400g of solid waste-based composite cementitious material prepared in Example 4, 600g of non-fired ceramsite prepared in Example 1, and 500g of iron tailings sand (fineness modulus of 2.55, particle size range between 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0087] Step 2: Add 100g of water and 5g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete.

[0088] Example 9

[0089] Step 1: Pour 500g of solid waste-based composite cementitious material prepared in Example 5, 800g of non-fired ceramsite prepared in Example 2, and 600g of iron tailings sand (fineness modulus of 2.55, particle size range between 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0090] Step 2: Add 167g of water and 7g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete.

[0091] Example 10

[0092] Step 1: Pour 440g of solid waste-based composite cementitious material prepared in Example 6, 755.3g of non-fired ceramsite prepared in Example 3, and 576.1g of iron tailings sand (fineness modulus of 2.55, particle size range of 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0093] Step 2: Add water and 6.5g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete;

[0094] In step two, the ratio of water to solid waste-based composite cementitious material (referred to as the water-cement ratio) is 0.30.

[0095] Example 11

[0096] Step 1: Pour 440g of solid waste-based composite cementitious material prepared in Example 6, 755.3g of non-fired ceramsite prepared in Example 3, and 576.1g of iron tailings sand (fineness modulus of 2.55, particle size range of 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0097] Step 2: Add water and 6.5g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete;

[0098] In step two, the ratio of water to solid waste-based composite cementitious material (referred to as the water-cement ratio) is 0.32.

[0099] Example 12

[0100] Step 1: Pour 440g of solid waste-based composite cementitious material prepared in Example 6, 755.3g of non-fired ceramsite prepared in Example 3, and 576.1g of iron tailings sand (fineness modulus of 2.55, particle size range of 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0101] Step 2: Add water and 6.5g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete;

[0102] In step two, the ratio of water to solid waste-based composite cementitious material (referred to as the water-cement ratio) is 0.34.

[0103] Example 13

[0104] Step 1: Pour 440g of solid waste-based composite cementitious material prepared in Example 6, 755.3g of non-fired ceramsite prepared in Example 3, and 576.1g of iron tailings sand (fineness modulus of 2.55, particle size range of 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0105] Step 2: Add water and 6.5g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete;

[0106] In step two, the ratio of water to solid waste-based composite cementitious material (referred to as the water-cement ratio) is 0.36.

[0107] Example 14

[0108] Step 1: Pour 440g of solid waste-based composite cementitious material prepared in Example 6, 755.3g of non-fired ceramsite prepared in Example 3, and 576.1g of iron tailings sand (fineness modulus of 2.55, particle size range of 0.15-4.75mm) into a concrete mixer and mix for 1 minute.

[0109] Step 2: Add water and 6.5g of the water-reducing agent prepared in Example 7 to the mixer in Step 1, and continue mixing for 1 minute to obtain lightweight concrete;

[0110] In step two, the ratio of water to solid waste-based composite cementitious material (referred to as the water-cement ratio) is 0.38.

[0111] Slump tests were conducted on the concrete obtained in Examples 10-14, which are listed from left to right as Examples 10-14. The experimental results are as follows: Figure 1 As shown;

[0112] Mechanical property tests were conducted on the concrete obtained in Examples 10-14. From left to right, Examples 10-14 are shown. The experimental results are as follows: Figure 2 As shown;

[0113] Early cracking performance tests were conducted on the concrete obtained in Examples 10-14. From left to right, Examples 10-14 are shown in the figures. The experimental results are as follows: Figure 3 As shown;

[0114] The concrete obtained in Example 14 and ordinary concrete were subjected to a compressive failure test. The failure modes are as follows: Figure 4 As shown;

[0115] Depend on Figure 1 It can be seen that the slump of concrete increases with the increase of the water-cement ratio. When the water-cement ratio increases from 0.30 to 0.32, the increase in concrete slump reaches its maximum value of 13.38%; when the water-cement ratio increases from 0.32 to 0.34, the concrete slump increases from 162 mm to 175 mm, an increase of 8.70%; when the water-cement ratio increases from 0.34 to 0.36 and 0.38, the increase in concrete slump is not significant in the two stages, at 6.29% and 4.3% respectively; when the water-cement ratio is 0.38, the concrete slump reaches its maximum value of 194 mm.

[0116] Depend on Figure 2 It can be seen that the compressive strength of the samples decreases with the increase of the water-cement ratio in concrete. At a water-cement ratio of 0.30, the compressive strength of concrete at 3d, 7d, and 28d all reach their maximum values, which are 26.8 MPa, 31.4 MPa, and 32.4 MPa, respectively. At a water-cement ratio of 0.38, the compressive strength of concrete at 3d, 7d, and 28d all reach their minimum values, which are 20.8 MPa, 25.9 MPa, and 27.3 MPa, respectively. Comparing the 3d compressive strength longitudinally, when the water-cement ratio increases from 0.30 to 0.38, the decrease in 3d compressive strength reaches its maximum of 22.39%, indicating that the water-cement ratio has a significant impact on the early strength of concrete. The test results also show that when the water-cement ratio decreases from 0.38 to 0.36, the 28-day compressive strength of concrete increases from 27.3 MPa to 27.9 MPa, a relatively small change. Cross-testing revealed that the 28-day compressive strength of solid waste-based cementitious materials at water-cement ratios of 0.38 and 0.36 were similar.

[0117] Depend on Figure 3 It can be seen that when the water-cement ratio increases from 0.30 to 0.34, the cracked area of ​​the concrete increases from 588 mm². 2 dropped to 435mm 2 The water-cement ratio decreased by 26.02%, but when the water-cement ratio continued to rise from 0.34 to 0.38, the cracked area of ​​the concrete began to increase, although the increase was relatively small. This is because when the water-cement ratio increases within a small range, more water molecules migrate from the inside of the concrete to the surface, the shrinkage force in the system decreases sharply, the autogenous shrinkage phenomenon is delayed, and the early crack resistance of the concrete is improved. However, when the water-cement ratio continues to increase, the fluidity of the concrete increases, the cohesiveness decreases, and the settlement of coarse aggregates increases the risk of cracking, thus causing the concrete to crack.

[0118] Based on a comprehensive analysis of the slump, compressive strength, and early cracking performance of solid waste-based lightweight concrete, the concrete exhibits the highest 28-day compressive strength when the water-cement ratio is 0.30, but the slump is too low and the concrete's flowability is poor. The early cracking resistance is better when the water-cement ratio is 0.32. Therefore, a water-cement ratio of 0.32 is selected to prepare solid waste-based lightweight concrete.

[0119] Depend on Figure 4As shown in a and 4b, cracks in ordinary concrete are mostly diagonal, while cracks in waste-based lightweight concrete are mostly longitudinal. With pressure reaching its peak, cracks in ordinary concrete extend diagonally from the top to the bottom, accompanied by a popping sound, and spalling occurs around the perimeter of the specimen. In contrast, cracks in waste-based lightweight concrete extend longitudinally from the top to the bottom, and the specimen is supported by friction between the remaining parts, without significant spalling or deformation. This indicates that the failure mode of ordinary concrete is diagonal shear failure, while the failure mode of waste-based lightweight concrete is longitudinal splitting failure. The reason is that ordinary concrete uses waste stone as coarse aggregate, which bonds with cement paste. However, since the strength of the waste stone and cement paste is higher than the strength of the interface transition zone between them, when external force is applied, the interface transition zone will be destroyed first, and cracks will extend along the interface transition zone, forming shear failure. Waste-based lightweight concrete mainly uses expanded clay as coarse aggregate. Since the strength of expanded clay is lower than that of cement paste, external force will destroy the expanded clay first, thus producing longitudinal cracks. Figure 4 a and 4b also show that the cracks in solid waste-based lightweight concrete are finer than those in ordinary concrete. This is because the expanded clay aggregate is evenly distributed inside the concrete and has a smoother surface, which can prevent crack propagation. The inclined shear failure of ordinary concrete is due to the destruction of the interface transition zone, while the longitudinal splitting failure of solid waste-based lightweight concrete is caused by the longitudinal penetration of the expanded clay aggregate. Furthermore, the cracks in solid waste-based lightweight concrete are finer, indicating lower brittleness.

[0120] In summary, Example 10 of this invention provides lightweight concrete prepared with an optimal water-cement ratio, and the dry apparent density of this concrete is 1869 kg / m³. 2 The slump was 150 mm, and the compressive strengths at 3 days, 7 days, and 28 days reached 25.9 MPa, 27.9 MPa, and 36.5 MPa, respectively. The total area of ​​early cracking was 108 mm². 2 Compared to ordinary cement concrete, it is lighter, has better fluidity, and higher strength, making it suitable for construction scenarios with special requirements for weight and strength, and possessing significant application value in the field of concrete technology.

[0121] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0122] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A method for preparing lightweight concrete, characterized in that, Includes the following steps: Step 1: Pour the solid waste-based composite cementitious material, non-fired ceramsite, and iron tailings sand into a concrete mixer and mix for 1-2 minutes; Step 2: Add water and water-reducing agent to the mixer from Step 1, and continue mixing for 1-2 minutes to obtain lightweight concrete; The water-reducing agent is prepared through the following steps: Step B1: Add viscous acid, 2-naphthylamine and N,N-dimethylformamide to a flask, stir and mix, then add dicyclohexylcarbodiimide, and the reaction is completed at 45°C for 5 hours to obtain reaction product 1. Step B2: Add reaction product 1, allylamine and N,N-dimethylformamide to a flask, stir and mix, then add dicyclohexylcarbodiimide, and react at 55°C for 7 hours. The reaction is complete, and reaction product 2 is obtained. Step B3: Add isobutylene polyoxyethylene ether, isopentenyl alcohol polyoxyethylene ether and deionized water to the flask and stir continuously to dissolve; mix L-ascorbic acid, mercaptoacetic acid and deionized water as material A, then weigh acrylic acid and deionized water and mix them as material B; add ammonium persulfate and reaction product 2 to the four-necked flask, stir, and then start adding materials A and B dropwise over a period of 4 hours. After the addition is complete, keep the temperature at 45°C for 3 hours to obtain the water-reducing agent. In step B1, the ratio of the amounts of viscous acid, 2-naphthylamine, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 23.7g:14.3g:100mL:20.6g; in step B2, the ratio of the amounts of reaction product 1, allylamine, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 33.5g:5.7g:100mL:20.6g; and in step B3, the ratio of the amounts of isobutylene polyoxyethylene ether, isopentenyl alcohol polyoxyethylene ether, ascorbic acid, mercaptoacetic acid, acrylic acid, ammonium persulfate, and reaction product 2 is 50.0g:25.0g:3.7g:1.3g:11.3g:2.2g:9.7g.

2. The method for preparing lightweight concrete according to claim 1, characterized in that, The raw materials are as follows by weight: 400-500 parts solid waste-based composite cementitious material, 600-800 parts non-fired ceramsite, 500-600 parts iron tailings sand, 100-200 parts water and 5-7 parts water-reducing agent.

3. The method for preparing lightweight concrete according to claim 1, characterized in that, The iron tailings sand in step one is used as fine aggregate with a fineness modulus of 2.55 and a particle size range of 0.15-4.75 mm.

4. The method for preparing lightweight concrete according to claim 1, characterized in that, The non-fired ceramsite is prepared through the following steps: Step A1: Place the ground fly ash, iron tailings and desulfurized gypsum in an oven at 60-80℃ and dry to constant weight. After cooling, you will get the dried fly ash, iron tailings and desulfurized gypsum. Step A2: Mix the dried fly ash, dried iron tailings, dried desulfurized gypsum, quicklime and sodium silicate evenly to obtain the basic materials for preparing ceramsite. Step A3: Turn on the disc granulator, sprinkle a small amount of the basic material obtained in step A2 on the top of the disc granulator, fix the angle of the pelletizing disc at 60°, control the rotation speed at 40-50 r / min, add water to the material in the granulator with a spray bottle, observe the degree of material adhesion, and then continue to add the remaining basic material and water to the granulator to obtain pelletized ceramsite. Step A4: Remove the pelletized ceramsite from the pelletizing tray and allow it to cure. Once the ceramsite has stabilized, place it in a square-hole sieve with different aperture sizes for sieving to obtain non-fired ceramsite.

5. The method for preparing lightweight concrete according to claim 4, characterized in that, The raw materials are as follows by weight: 38-42 parts dried fly ash, 38-42 parts dried iron tailings, 8-12 parts dried desulfurized gypsum, 4-6 parts quicklime, and 4-6 parts sodium silicate.

6. The method for preparing lightweight concrete according to claim 4, characterized in that, In step A3, the small amount of basic material is 1 / 10 of the total mass of basic materials.

7. The method for preparing lightweight concrete according to claim 1, characterized in that, The solid waste-based composite cementitious material is prepared through the following steps: The slag powder is dried in an oven, and then the dried slag powder is mixed evenly with steel slag, cement and desulfurized gypsum to obtain a solid waste-based composite cementitious material.

8. The method for preparing lightweight concrete according to claim 7, characterized in that, The raw materials are as follows by weight: 48-52 parts dried slag powder, 8-12 parts steel slag, 28-32 parts cement, and 8-12 parts desulfurized gypsum.

Citation Information

Patent Citations

  • A kind of ultra-high strength concrete with low shrinkage and low viscosity

    CN104844099B

  • Red mud-based ceramsite concrete and preparation method and application thereof

    CN111302746A

  • Iron tailing unfired ceramsite and preparation method thereof

    CN112794666A

  • Rapid pavement repairing material

    CN114180933A

  • Desulfurized gypsum-mineral powder based high-strength lightweight aggregate concrete material and preparation method thereof

    CN118666555A